2011
DOI: 10.1002/jclp.20842
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction, perceived treatment effectiveness, and dropout among older users of mental health services

Abstract: Results from this study indicate that older adults have very good self-reported treatment outcomes. The modest influence of individual characteristics on treatment outcomes suggests the potential importance of contextual characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
33
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 52 publications
(65 reference statements)
8
33
1
Order By: Relevance
“…To date, no studies have considered the impact of loneliness on patient satisfaction. However, our results are consistent with other studies that have demonstrated that anxiety (Hundt et al, 2013; Stein et al, 2011) and mental health treatments (Chen et al, 2006; Hasler et al, 2004; Lippens & Mackenzie, 2011) are often associated with reduced patient satisfaction. In these studies, symptom improvement and social support played a significant role in both treatment satisfaction and perceived effectiveness (Hasler et al, 2004; Hundt et al, 2013; Lippens & Mackenzie, 2011; Shea et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…To date, no studies have considered the impact of loneliness on patient satisfaction. However, our results are consistent with other studies that have demonstrated that anxiety (Hundt et al, 2013; Stein et al, 2011) and mental health treatments (Chen et al, 2006; Hasler et al, 2004; Lippens & Mackenzie, 2011) are often associated with reduced patient satisfaction. In these studies, symptom improvement and social support played a significant role in both treatment satisfaction and perceived effectiveness (Hasler et al, 2004; Hundt et al, 2013; Lippens & Mackenzie, 2011; Shea et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…That older CGMs were more compliant than younger CGMs is in line with findings in the mental health literature that older age is associated with lower dropout rates, presumably because older persons are more likely to trust service providers and to adhere to their recommendations (Lippens & Mackenzie, 2011). It is also likely that older CGMs give care to older CGCs, which may explain why compliance was higher at the univariate level among CGMs who were caring for older children.…”
Section: Discussionsupporting
confidence: 81%
“…Our use of Andersen’s (2008) model is consistent with that of Lippens and Mackenzie (2011), who employed it uniquely to examine treatment satisfaction and dropout among older users of mental health services. The categorization of study variables according to the Andersen model is shown in Tables 1 and 3.…”
mentioning
confidence: 57%
See 2 more Smart Citations